Portaria PGR/MPF nº 1.126, de 24 de outubro de 2017 - Raquel Elias Ferreira Dodge (DOU, Brasília, DF, 26 out. 2017. Seção 2, p.46., 2017)
Altera o art. 3º da Portaria PGR nº 849, de 26 de novembro de 2013.